Simulation Study on Driving Force Distribution Pattern and Four-wheel Independent Drive System - Chi Peng; Wang Shukun (Jixie chuandong)
In order to improve the efficiency of driving force and the control ability of special vehicle,dynamic performance and stability,the distribution pattern of the four-wheel independent drive system is studied. A platform physical model with four-wheel independent drive is set up according to the real vehicle structure,and the virtual prototype model is built based on the ADAMS software. Through dynamics simulation under three driving force distribution modes of vehicle on straight road vehicle condition,the influence of vehicles running state is analyzed with equal torque and equal state driving force distribution model,and the influence factors of vehicle running deviation is studied with different wheel torque mode. The simulation results show that the drive torque optimal allocation proportion is associated with the location of the center of mass and equal state pattern is better. When the vehicle driving torque is not equal,vehicle running deviation degree mainly depends on the difference between left and right sides of the driving force.